Effect Of Operating Parameters In Stirred Mill For Filler Production - Yusof, Mohd Shafiq Mohd (Universiti Sains Malaysia, 2017)
Stirred mill has becomes popular recently for fine grinding as it is more efficient than conventional ball mill. Sympatec particle size analyser was used to identify the size distribution of the limestone after grinding by stirred mill. The aim of this work is to investigate the effects of the operating parameters on grinding rate and the size of products. The operating parameters had been investigated in this work were stirrer speed, solids concentration and media filling. Grinding performance was assessed by analysing the particle size reduction and the size of the products. The grinding rate and grinding efficiency increases when the stirrer speed and solids concentration were increases. Meanwhile, for media filling ratio, the grinding efficiency and grinding rate increases if the media filling increases until an optimum level which the media filling increases passes the optimum level, the grinding efficiency and grinding rate decreases. In my study, stirrer speed of 160 revolutions per minute (rpm) and solids concentration of 70% had higher grinding efficiency and higher grinding rate. Meanwhile, media filling of 0.9 had higher grinding efficiency and higher grinding rate for size higher than 8.60 μm and lower grinding efficiency and lower grinding rate for size lower than 8.60 μm.